Kontrak Kerja vs Kontrak Platform : Perbandingan Perlindungan Hukum bagi Pekerja di Era Ekonomi Digital - Rahma Fitri Amelia Hasibuan; Muhammad Abdillah; Nadilah Andini; Fitria Mukhtar Siregar; Annisa Putri Andini Tanjung (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The rapid development of the digital economy has transformed the labor landscape with the emergence of a new type of employment contract known as platform contracts, which differ from conventional formal employment contracts. This phenomenon poses significant challenges regarding legal protection for workers, especially in ensuring basic rights and social justice in the digital era. This study aims to analyze the comparison of legal protection between workers bound by formal employment contracts and digital platform workers. The research method used is qualitative descriptive with a literature review from various relevant primary and secondary sources. The results reveal that formal workers receive stronger and more comprehensive legal protection through existing labor regulations, whereas platform workers face legal status ambiguity, leading to minimal protection and risks of exploitation. This study emphasizes the importance of adaptive legal reforms to accommodate changes brought by the digital economy by expanding the definition of workers and providing equal legal protection for platform workers. In conclusion, regulatory updates and collaboration among various stakeholders are necessary to create a fair and sustainable work ecosystem in the digital era.